2020
DOI: 10.1021/acsami.9b22293
|View full text |Cite
|
Sign up to set email alerts
|

Nanovector Assembled from Natural Egg Yolk Lipids for Tumor-Targeted Delivery of Therapeutics

Abstract: Nanomedicine uses nanotechnology-based strategies for precision tumor therapy, including passive and ligand-mediated active tumor targeting by nanocarriers. However, the possible biotoxicity of chemosynthetic nanovectors limits their clinical applications. A novel natural egg yolk lipid nanovector (EYLN) was developed for effective loading and delivery of therapeutic agents. Lipids were extracted from egg yolks and reassembled into nanosized particles. EYLNs’ stability, cellular uptake, toxicity, and delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…EYLNs and EYLNs-Dox were prepared according to the protocol described in our previous publication. 14 In brief, dried lipids[phosphatidylcholine (PC, 75.5%), sphingomyelin (SM, 12.7%), lysophosphatidylcholine (LPC, 6.55%), phosphatidylethanolamine (PE, 4.37%), phosphatidylinositol (PI, 0.54%), and phosphatidylglycerol (PG, 0.34%)] were suspended in distilled water (200-400 μL) and Dox solution (1 mg/mL), respectively, and the suspension was sonicated for 15-20 min using an FS60 bath sonicator (Fisher Scientific). The non-loaded Dox was removed by centrifugation at 100,000 × g for 30 min.…”
Section: Eylns and Eylns-dox Preparation And Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…EYLNs and EYLNs-Dox were prepared according to the protocol described in our previous publication. 14 In brief, dried lipids[phosphatidylcholine (PC, 75.5%), sphingomyelin (SM, 12.7%), lysophosphatidylcholine (LPC, 6.55%), phosphatidylethanolamine (PE, 4.37%), phosphatidylinositol (PI, 0.54%), and phosphatidylglycerol (PG, 0.34%)] were suspended in distilled water (200-400 μL) and Dox solution (1 mg/mL), respectively, and the suspension was sonicated for 15-20 min using an FS60 bath sonicator (Fisher Scientific). The non-loaded Dox was removed by centrifugation at 100,000 × g for 30 min.…”
Section: Eylns and Eylns-dox Preparation And Characterizationmentioning
confidence: 99%
“…[11][12][13] In this study, a model anti-cancer chemotherapeutic drug (doxorubicin)-loaded, natural purified egg yolk lipidderived nanovector (EYLNs-Dox) was developed, EYLNs nanovector has been demonstrated a promising drug carrier due to the low toxicity and strong EPR effect. 14 EYLNs-Dox was internalized in macrophages to prepare a macrophage-based biomimetic drug delivery system (Mac/EYLNs-Dox). The tumor penetration and inhibitory effects of Mac/EYLNs-Dox were evaluated in vitro and the tumor targeting ability and anti-tumor efficacy of Mac/ EYLNs-Dox were evaluated using a 4T1 mouse breast cancer model.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that EY has mostly been investigated for drug delivery applications, , its application to TE has been reported in limited studies. For example, Charbonneau et al investigated the combination of EY plasma with EW hydrogel for salivary gland TE .…”
Section: Egg Yolkmentioning
confidence: 99%
“…Application of folic acid (FA)-modified natural egg yolk lipid nanovector (EYLNs) load with DOX (FA-EYLNs-DOX) showed higher encapsulation efficiency and were effectively taken up by cancer cells without obvious toxicity in vitro and in vivo. In addition, FA-EYLNs-DOX showed that FA significantly achieved better tumor targeting of EYLNs-DOX [ 140 ].…”
Section: Application and Clinical Trials Of Nanocarrier-based Thermentioning
confidence: 99%